Merchants and networks from the Bolivian port of Cobija - Conti, Viviana E. (2018)
The article focuses on the Bolivian port of Cobija, during its brief operation in the historical context of South America. Its role as a link between the world market and the urban and mercantile centers of the interior of the continent, which in turn distributed the goods in the interior of the South-Andean space is highlighted. The construction of mercantile networks and the commercial practices of the port of Lamar are dealt with and the mercantile sectors are identified and qualified according to the amounts of the transactions carried out with overseas goods entered to the customs. The research uses new sources on topics already addressed.